Latest developments in chronic total occlusion percutaneous coronary intervention. (2nd July 2020) - Nikolakopoulos, Ilias; Vemmou, Evangelia; Karacsonyi, Judit; Xenogiannis, Iosif; Werner, Gerald S.; Gershlick, Anthony H.; Rinfret, Stephane; Yamane, Masahisa; Avran, Alexandre; Egred, Mohaned; Garcia, Santiago; Burke, M. Nicholas; et al.
ABSTRACT: Introduction: Chronic Total Occlusion Percutaneous Coronary Intervention (CTO PCI) is now performed with high success rates and acceptable complication rates. Areas covered: We describe recent clinical and technological developments in CTO PCI from 2018 to 2020. Expert opinion: After publication of six randomized controlled trials, improving patient symptoms remains the principal indication for CTO PCI. Although good outcomes can be achieved with CTO PCI at experienced centers, success rates are significantly lower at less experienced centers, despite increased use in CTO crossing algorithms and development of novel and improved equipment and techniques.